The Role of Analog and Digital Media as a Playground to Support Children’s Development - Sabiela, Yaritsa Husni; Pratiwi, Diyan Tresna; Wardono, Prabu; Ratri, Dianing (Jurnal Pendidikan Anak, 2022)
Exploration of play in childhood is very important in child development.One of the environments that can support children’s developmentis the play environment. So far,many children’s play environmentuses analog playing media. However,with the development ofspaceand technology,the formation of space is increasingly diverse.Oneof them is a combination of space with video mapping. Videomappingis implemented in the playroom so that it can open new exploratoryinteractions for children. Children with an age range of 5–7yearsbecome the subject of this study as a development of previousresearchand at that age, children begin to recognize and understandthephysical environment around them so that they can form a behavior.This study aims to determine the role of analog media and videomappingin play facilities that can stimulate children aged 5–7 years toexploreplay to encourage child development. This research methodusesSpatial Affordancesin Childcare Interior Design (SACID)as theinstrumentfor calculating the breadth and depth of affordance explorationwith the basic theory of Gibson’s observation, perception-actionaffordance.The results show that there is more variation in the spatialcomponentsof analog media than in video mapping media. However,interms of depth, video mapping is stronger.While the breadth of thetwomedia shows a fairly high exploration. This study shows that bothmediacan support children’s development with the different potentialofeach exploration that occurs between analog media space and videomapping.Based on these findings, this research can be considered inchoosingthe use of analog media or video mapping in the early childhoodplayroom.